The role of sense of coherence in the relationship between levels of physical activity and self-esteem among students - Lordan, John Sebastiaan (University of the Free State, 2018)
Sense of coherence (SOC) forms part of the positive psychology paradigm and offers insight into many contexts related to the health-disease continuum. Physical activity can easily be connected to this equation as the health benefits of physical activity are well known. Alternatively, self-esteem incorporates a psychological construct that can be influenced by multiple factors found in one’s biological, psychological, social and spiritual environments. Furthermore, the emerging adulthood population, which includes university students, is described as being an age of possibilities in various domains of functioning, and therefore makes this an interesting age group on which to conduct research. Hence, the aim of this study is to investigate the role of SOC on the relationship between physical activity and self-esteem among students. A non-experimental quantitative approach, in accordance with a correlational research design, was used to conduct this study. A sample of 196 student participants between the ages of 18-25 currently studying at The University of the Free State in South Africa were included through a non-probability, convenience type sampling method. This sample comprised of 106 (54.1%) female and 90 (45.9%) male students. Three groups were formed for statistical purposes namely: males, females and a total group. Self-report questionnaires formed a battery of measuring instruments to collect data. This battery included the Physical Activity Questionnaire for Adults (PAQ-AD) to measure physical activity levels, the Rosenberg Self-Esteem Scale (RSE) to measure global self-esteem, and the Orientation to Life Scale (29 items, SOC-29) to measure SOC. Biographical information was obtained through a biographical section subsumed within the PAQ-AD. Results yielded, a significant positive relationship of .193 for the total group regarding physical activity and self-esteem. However, discrepancies were obtained when the total group was split according to gender. A significant positive relationship of .219 was found for male students with regard to the relationship between these two variables, but not for female students. Results suggest that significant positive relationships exist between self-esteem and SOC for all three groups. Furthermore, significant positive correlations were found between physical activity and SOC for all three groups. Lastly, while no mediating/ moderating effect could be obtained for the role of SOC on the relationship between physical activity and self-esteem in female students, SOC was identified to have a mediating role on the relationship between these variables in male students. In conclusion, key findings suggest that gender accounts for variances among male and female students in the relationship between physical activity and self-esteem. Furthermore, differences were observed in terms of the role of SOC in respect to physical activity and self-esteem when investigated for male and female students independently.

Koherensiesin is ’n konstruk wat deel uitmaak van die positiewe sielkunde-paradigma. Hierdie konstruk bied dus insig ten opsigte van aspekte wat verband hou met die kontinuum waarop gesondheid en siekte gemeet word. Fisiese aktiwiteit kan tot hierdie raamwerk gevoeg word, aangesien die voordele van fisiese aktiwiteit met menslike gesondheid verband hou en in die literatuur welbekend is. Laastens kan die sielkundige konstruk, selfbeeld, as ‘n veranderlike voorgestel word wat deur verskeie faktore binne die konteks van ‘n persoon se biologiese-, psigologiese-, sosiale-, en spirituele omgewings beïnvloed kan word. Verder word die ontluikende volwasse-bevolking, wat universiteitstudente insluit, in die literatuur voorgestel as ‘n ouderdom wat talle moontlikhede in verskeie areas van funksionering inhou. Daarom is dit ‘n interessante groep om op navorsing te doen. Hierdie studie het dit ten doel om die rol van koherensiesin in die verband tussen fisiese aktiwiteit en selfbeeld onder universiteitstudente te ondersoek. Hierdie studie het ‘n nie-eksperimentele, kwantitatiewe benadering gevolg, tesame met ‘n korrelasionele navorsingsontwerp. ‘n Steekproef van 196 studente, tussen die ouderdom van 18 en 25, en wat tans aan die Universiteit van die Vrystaat in Suid-Afrika studeer, is verkry. Hierdie steekproef is deur middel van ‘n nie-waarskynlikheids, gerieflikheidsteekproeftrekking gedoen. Die steekproef het altesaam uit 106 (54.1%) vroulike en 90 (45.9%) manlike studente bestaan. Ten einde data in te samel, is selfevalueringsvraelyste as toetsbattery gebruik. Hierdie toetsbattery het die volgende ingesluit naamlik: die “Physical Activity Questionnaire for Adults” (PAQ-AD) vir die meet van fisiese aktiwiteitsvlakke, die “Rosenberg Self-Esteem Scale” (RSE) vir die meet van globale selfbeeld, asook die “Orientation to Life Scale (29-items – SOC-29), ten einde koherensiesin (SOC) te meet. Biografiese inligting was bekom deur middel van biografiese vrae wat in die PAQ-AD bevat word. Resultate dui daarop dat daar ‘n beduidende, positiewe verband (.193) rakende fisiese aktiwiteit en selfbeeld, by die totale groep is. Verskille is egter in die totale groep, wat op grond van geslag verdeel is, waargeneem. ‘n Beduidende positiewe verband (.219) rakende die bogenoemde veranderlikes, is onder manlike studente gevind, maar nie onder vroulike studente nie. Resultate dui verder op beduidende postiewe verbande tussen selfbeeld en koherensiesin, sowel as fisiese aktiwiteit en koherensiesin onder al drie die groepe. Laastens, alhoewel koherensiesin nie as mediator-/ moderatorveranderlike in die verband tussen fisiese aktiwiteit en selfbeeld onder damestudente gevind kon word nie, kon hierdie veranderlike as mediatorveranderlike in die verband tussen fisiese aktiwiteit en selfbeeld by manlike studente geïdentifiseer word. Ten slotte is daar in hierdie studie bevind dat geslag tot verskille onder manlike en vroulike universiteitstudente bydra wanneer die verband tussen fisiese aktiwiteit en selfbeeld ondersoek word. Verder is verskille ook waargeneem toe die rol van koherensiesin, in hiérdie verband, afsonderlik vir mans- en damestudente ondersoek is.
Dissertation (M.Soc.Sc. (Clinical Psychology))--University of the Free State, 2018
Keywords: University; Students; Emerging adults; Physical activity; Exercise; Sport; Self-esteem; Self-concept; Sense of coherence; Salutogenesis